死を意識した終末期がん患者へのがん看護専門看護師の意図的な関わり - 小田 真理子; 国府 浩子 (日本がん看護学会誌, 2023)
要旨　本研究の目的は，死を意識した終末期がん患者へのがん看護専門看護師の意図的な関わりの内容を明らかにすることである．　がん看護専門看護師10名へ半構造化面接を実施し，得られたデータを質的帰納的に分析した．その結果，死を意識した終末期がん患者へのがん看護専門看護師の意図的な関わりとして，【患者のなかに身を投じる】【常にぶれない覚悟で対峙する】【意識を研ぎ澄まして患者のメッセージを感受する】【患者の終焉までの道のりを伴走する】【患者の大切なものを守り抜く】【患者が自らの力で踏み出していけるように導く】【患者を支える人と力を強固にする】【基盤となるケアを提供する】が導き出された．　がん看護専門看護師の関わりの特徴は，①死を意識した患者のなかに身を投じつつも常にぶれない姿勢と覚悟，②終焉までの道のりの伴走者としての役割の自覚，③その人らしい人生の完成へと導くサポート，④基盤となるケアの上に築かれる関わりであるととらえられた．　また，最期まで患者に関わり続けることができる看護師を育成するためには，がん看護専門看護師による教育を受ける機会や周囲のサポート体制の整備と強化が必要であることが示唆された． 　The purpose of this study was to elucidate the nature of the intentional involvement of oncology nurse specialists with end-of-life cancer patients who are aware of dying. We conducted semi-structured interviews with 10 oncology nurse specialists and analyzed the data obtained by qualitative induction. As a result, "Commit myself to the patient," "Always face the patient with an unwavering resolve," "Sharpen awareness and sense the patient's messages," "Accompany the patient on the journey to the end of life," "Protect the things that are important to the patient until the end," "Guide the patient in a way that enables the patient to proceed on his/her own," "Strengthen cooperation with people who support the patient," and "Provide underlying care," were concluded to be intentional involvements of oncology nurse specialists with end-of-life cancer patients who have become aware of dying. The characteristics of the involvement of the oncology nurse specialists were concluded to be: (1) a constant unwavering attitude and resolve, while committing oneself to patients who are aware of dying, (2) an awareness of playing the role of a companion on the patient's journey to the end of his/her life, (3) support that leads to the completion of the patient's life in the patient's own way, and (4) involvement built on underlying care. In addition, the results suggested that opportunities for education by oncology nurse specialists and developing and strengthening the surrounding support system are needed to train nurses who are capable of staying involved with their patient until the end of the patient's life.